Modulation of phagocytosis-induced cell death of human neutrophils by Neisseria gonorrhoeae. Issue 5 (25th September 2020) - Cho, Christine; Teghanemt, Athmane; Apicella, Michael A; Nauseef, William M
Abstract: Optimal innate immune response to infection includes eradication of potential pathogens, resolution of associated inflammation, and restitution of homeostasis. Phagocytosing human polymorphonuclear leukocytes (hPMN) undergo accelerated apoptosis, a process referred to as phagocytosis-induced cell death (PICD) and an early step in their clearance from inflammatory sites. Among human pathogens that modulate hPMN apoptosis, Neisseria gonorrhoeae delays PICD, which may contribute to the exuberant neutrophilic inflammation that characterizes gonorrhea. To elucidate the mechanisms underlying delayed PICD, we compared features of hPMN cell death that followed phagocytosis of N. gonorrhoeae FA1090 wild-type (GC) or serum-opsonized zymosan (OPZ), a prototypical stimulus of PICD. Phosphatidylserine externalization required NADPH oxidase activity after ingestion of GC or OPZ, and annexin V staining and DNA fragmentation were less after phagocytosis of GC compared to OPZ. Caspase 3/7 and caspase 9 activities after phagocytosis of GC were less than that seen after ingestion of OPZ, but caspase 8 activity was the same after ingestion of GC or OPZ. When hPMN sequentially ingested GC followed by OPZ, both caspase 3/7 and 9 activities were less than that seen after OPZ alone, and the inhibition was dose dependent for GC, suggesting that ingestion of GC actively inhibited PICD. Sequential phagocytosis did not block caspase 8 activity, mitochondrial depolarization, or annexin V/propidium iodide staining compared to responses of hPMN fed OPZ alone, despite inhibition of caspases 3/7 and 9. Taken together, these data suggest that active inhibition of the intrinsic pathway of apoptosis contributes to the delay in PICD after hPMN ingestion of N. gonorrhoeae . Graphical Abstract: Neisseria gonorrhoeae modifies caspase activation and mitochondrial depolarization in human neutrophils to modulate phagocytosis-induced cell death